Olmesartan Prevents Microalbuminuria in db/db Diabetic Mice Through Inhibition of Angiotensin II/p38/SIRT1-Induced Podocyte Apoptosis - Junhui Gu; Ming Yang; Na Qi; Shuqin Mei; Jiejian Chen; Shuwei Song; Ying Jing; Meihan Chen; Liangliang He; Lijun Sun; Huimin Hu; Lin Li; et al. (Karger Publishers, 2016)
Background/Aims: Blockage of the renin-angiotensin II system (RAS) prevents or delays albuminuria in diabetic patients. The aim of this study was to investigate the inhibitory mechanism of the angiotensin receptor blocker olmesartan on albuminuria in a murine model of diabetic nephropathy. Methods: Male db/db diabetic mice were fed with placebo or 20 mg/kg olmesartan by daily gavage for 12 weeks. Conditionally immortalized mouse podocytes were treated with glucose, angiotensin II, olmesartan or p38 inhibitor s8307 in different experimental conditions after differentiation. Results: Olmesartan reduced albuminuria in db/db mice without change in body weight and glycemia. The increase of apoptotic cells and decrease of podocytes in the diabetic glomerulus were prevented by olmesartan. Moreover, olmesartan restored silent mating type information regulation 1 (SIRT1) expression in diabetic glomeruli. Furthermore, olmesartan treatment suppressed p38 phosphorylation but did not restore adenosine 5'-monophosphate-activated protein kinase (AMPK) phosphorylation in the diabetic glomerulus. In vitro study revealed that olmesartan prevented angiotensin II/p38/SIRT1 induced podocyte apoptosis, but it only slightly prevented high glucose/AMPK/SIRT1 induced podocyte apoptosis. In addition, the p38 inhibitor s8307 reversed SIRT1 expression and angiotensin II induced podocyte apoptosis. Conclusions: Olmesartan reduced albuminuria in diabetic nephropathy through inhibiting angiotensin II/p38/SIRT1 triggered podocyte apoptosis.